HPSG 2005 - The 12th International Conference on Head-Driven Phrase Structure Grammar: Conference Notes - Branco, António Horta (2009)
This technical report collects the extended abstracts selected for presentation at HPSG 2005 - The 12th International Conference on Head-Driven Phrase Structure Grammar (University of Lisbon, August 23-24, 2005 - http://hpsg2005.di.fc.ul.pt/) by the corresponding program committee